The house of wings - Byars, Betsy Cromer; Schwartz, Daniel 1929- . (New York Puffin Books, 1982)
Left with his grandfather until his parents are settled in Detroit, Sammy learns to respect and love the old man as they care for an injured crane together.
Ages 8-12.
Reprint. Originally published: New York : Viking Press, 1972.
Keywords: Cranes (Birds) -- Fiction; Grandparents -- Fiction